Embryonic Development of Parthenogenetic and Sexual Eggs in Lower Termites - Xin Peng; Zahid Khan; Xiao-Min Liu; Shi-Lin Deng; Yong-Gang Fang; Min Zhang; Xiao-Hong Su; Lian-Xi Xing; Xing-Rong Yan (Insects, 2023)
Worldwide, termites are one of few social insects. In this research, the stages of embryonic development in the parthenogenetic and sexual eggs of Reticulitermes aculabialis and R. flaviceps were observed and described. In R. flaviceps, the egg development of the FF and FM groups happened during the early phases of development, whereas in R. aculabialis, this appeared mainly during the late phase of development. The variance in the number of micropyles between the R. flaviceps FF colony type and the R. aculabialis FF colony type was statistically significant. Five stages of egg development were found in both types of R. aculabialis but only the sexual eggs of R. flaviceps. In R. flaviceps, 86% of the parthenogenetic eggs stopped growing during the blastoderm development, with the yolk cell assembling frequently in the center of the egg. According to the results of the single-cell transcriptome sequencing, we investigated the egg-to-larval expression level of genes (pka, map2k1, mapk1/3, hgk, mkp, and pax6) and indicated that the levels of essential gene expression in RaFF were considerably higher than in RfFF (p < 0.05). We also discovered that the oocyte cleavage rate in the FF colony type was considerably lower in R. flaviceps compared to R. aculabialis, which gave rise to a smaller number of mature oocytes in R. flaviceps. During ovulation in both species, oocytes underwent activation and one or two cleavage events, but the development of unfertilized eggs ceased in R. flaviceps. It was shown that termite oocyte and embryonic development were heavily influenced by genes with significant expressions. Results from the databases KEGG, COG, and GO unigenes revealed the control of numerous biological processes. This study is the first to complete a database of parthenogenetic and sexual eggs of R. flaviceps and R. aculabialis.